Influence of Natural Gas Hydrate Distribution Patterns on the Macroscale–Mesoscale Mechanical Properties of Hydrate-Bearing Sediments - Yujing Jiang; Xiaoyu Du; Peng Yan; Meng Li; Hengjie Luan; Xianzhuang Ma; Yichen Shi (Journal of Marine Science and Engineering, 2023)
Studying the mechanical characteristics of hydrate-bearing sediments (HBS) contributes to the comprehensive understanding of the mechanical behavior in environments with natural gas hydrate (NGH) occurrences. Simultaneously, the distribution patterns of hydrates significantly influence the strength, deformation, and stability of HBS. Therefore, this paper employs particle flow code (PFC) to conduct biaxial discrete element simulations on specimens of HBS with different hydrate distribution patterns, revealing the macroscale–mesoscale mechanical properties, evolution patterns, and destructive mechanisms. The results indicate that the strain-softening behavior of HBS specimens strengthens with the increase in hydrate layer thickness, leading to higher peak strength and E50 values. During the gradual movement of the hydrate layer position (Ay) from both ends to the center of the specimen (Ay = 0.40 mm → Ay = 20 mm), the strain-softening behavior weakens. However, when Ay = 20 mm, the specimen exhibits evident strain-softening behavior again. Moreover, with an increase in the angle between the hydrate layer and the horizontal direction (α) greater than 20°, the peak strength of the specimen increases, while E50 shows an overall decreasing trend. The influence of axial loads on the hydrate layer in specimens varies with α, with larger contact forces and fewer cracks observed for higher α values.